2014
DOI: 10.1037/a0030977
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness: Origins in childhood?

Abstract: In this review, we evaluate developmental and personality research with the aim of determining if the personality trait of conscientiousness can be identified in children and adolescents. After concluding that conscientiousness does emerge in childhood, we discuss the developmental origins of conscientiousness with a specific focus on self-regulation, academic motivation, and internalized compliance/internalization of standards. Based on the accumulated body of evidence, we conclude that self-regulation foster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
203
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(219 citation statements)
references
References 196 publications
(302 reference statements)
8
203
1
Order By: Relevance
“…A strong start at school often places students in upper tracks (as a matter of explicit policy or, increasingly, de facto), which, in turn, promotes educational achievements independent of the children's "inherited" aptitudes, preferences, and temperaments (Entwisle, Alexander, & Olson, 2004). Eisenberg, Duckworth, Spinrad, and Valiente (2014) noted the central role that children's self-regulation plays in the emergence of C. Given this developmental pattern, it is unsurprising that children's self-control and self-regulatory skills predict health later in life through a variety of pathways including decreasing the likelihood of succumbing to "adolescent snares," increasing the likelihood of engaging in a wide variety of health promoting behaviors throughout childhood and adolescence, and fostering the emergence of robust psychological, social and cultural capital.…”
Section: Processes In Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong start at school often places students in upper tracks (as a matter of explicit policy or, increasingly, de facto), which, in turn, promotes educational achievements independent of the children's "inherited" aptitudes, preferences, and temperaments (Entwisle, Alexander, & Olson, 2004). Eisenberg, Duckworth, Spinrad, and Valiente (2014) noted the central role that children's self-regulation plays in the emergence of C. Given this developmental pattern, it is unsurprising that children's self-control and self-regulatory skills predict health later in life through a variety of pathways including decreasing the likelihood of succumbing to "adolescent snares," increasing the likelihood of engaging in a wide variety of health promoting behaviors throughout childhood and adolescence, and fostering the emergence of robust psychological, social and cultural capital.…”
Section: Processes In Childhoodmentioning
confidence: 99%
“…Adolescent and adult C likely emerge from childhood temperament, especially sense of constraint, effortful control, and the inhibition of impulsive tendencies, as well as exposure to C behaviors in parents and other socializers (Eisenberg et al, 2014;Hampson, 2012). A substantial body of evidence suggests that childhood disinhibition and impulsivity are associated with externalizing behaviors, including life course persistent antisocial behaviors, and alcohol and substance use beginning in adolescence (see Roberts et al, 2009, for an overview).…”
Section: Processes In Childhoodmentioning
confidence: 99%
“…Some studies have clarified the direction of influence by Running Head: ADOLESCENT PERSONALITY AND UNEMPLOYMENT 6 examining traits measured before the respondents accumulated substantial labor market experience; for example Daly, Delaney, Egan, and Baumeister (2015) showed that more selfcontrolled children tend to experience less unemployment as adults. Self-controlled children are thought to better internalize and comply with standards and norms for behavior in order to become more conscientious adolescents (Eisenberg, Duckworth, Spinrad, & Valiente, 2014).…”
mentioning
confidence: 99%
“…For instance, school programs which promote attentional control, patience and forwardlooking behavior (Diamond & Lee, 2011) may be effective ways of producing lasting changes in conscientiousness (Eisenberg et al, 2014). This may in turn reduce later unemployment levels, although there is not yet strong evidence that such programs improve long-run labor market outcomes.…”
mentioning
confidence: 99%
“…As reviewed by Eisenberg, Duckworth, Spinrad, & Valiente (2013) in this issue, there is clear evidence that the broad constellation of behaviors and attitudes that typically fall under the common latent factor of conscientiousness in adults can also be identified at least at school-age if not earlier (Goldberg, 2001;that there are consistent and coherent links between aspects of temperament-particularly effortful control and positive affectivity-and conscientiousness in childhood (Halverson et al, 2003). While one might consider childhood personality and temperament to be partially overlapping sets of indicators best conceptualized at the same level of analysis, a causal-developmental perspective encourages a consideration of more complex inter-relationships, beyond the statistical correlations among trait indicators at a given point in time.…”
mentioning
confidence: 99%